I don’t like crickets, I love them: invertebrates are an important prey source for varanid lizards - Cross, Sophie; Craig, M.D.; Tomlinson, Sean; Bateman, Bill (WILEY, 2020)
Minimal annual rainfall in arid environments results in low productivity ecosystems with fluctuating food availability. Large mammalian predators that require frequent consumption of vertebrate prey tend to be less abundant in desert environments; however, such environments often support numerous large-bodied carnivorous reptiles. Diet is a fundamental component of an animal’s ecology, and we explore the diets of three coexisting, sympatric Varanus species occurring in arid Australia: V. tristis, V. gouldii and V. panoptes. We hypothesized that the diet of varanids living in arid environments would primarily consist of relatively abundant invertebrate prey, and that vertebrate prey items would largely be limited to opportunistically consumed mammalian carrion and small reptilian species. All three Varanus species had high dietary overlap and broad, generalist diets. Invertebrate prey, particularly Orthoptera, were key to the diets of all three species. Vertebrate prey was infrequently consumed by all three Varanus species; however, when consumed, tended to comprise small reptilian species and mammalian carrion. Unlike large mammalian predators, varanids can survive on invertebrate prey and infrequent feeds and can aestivate when conditions become unfavourable, contributing to their success in arid environments.